Why Do Emerging Economies Borrow in Foreign Currency? - Jeanne, Olivier (IMF Working Papers; Working Paper ;, 2003)
This paper explores the hypothesis that the dollarization of liabilities in emerging market economies is the result of a lack of monetary credibility. I present a model in which firms choose the currency composition of their debts so as to minimize their probability of default. Decreasing monetary credibility can induce firms to dollarize their liabilities, even though this makes them vulnerable to a depreciation of the domestic currency. The channel is different from the channel studied in the earlier literature on sovereign debt, and it applies to both private and public debt. The paper presents some empirical evidence and discusses policy implications.